Impacts of 5d electron binding energy and electron–phonon coupling on luminescence of Ce3+ in Li6Y(BO3)3. Issue 14 (11th March 2019) - Ou, Yiyi; Zhou, Weijie; Hou, Dejian; Brik, Mikhail G.; Dorenbos, Pieter; Huang, Yan; Liang, Hongbin
Abstract : The critical issues of Ce 3+ luminescence including thermal stability and spectral profile are discussed in this work. Abstract : In this work, the crystal structure and electronic structure as well as the synchrotron radiation vacuum ultraviolet-ultraviolet-visible (VUV-UV-vis) luminescence properties of Li6 Y(BO3 )3 (LYBO):Ce 3+ phosphors were investigated in detail. The Rietveld refinement and DFT calculation reveal the P 21 / c monoclinic crystal phase and the direct band gap of the LYBO compound, respectively. Only one kind of Ce 3+ 4f–5d transition is resolved in terms of the low temperature VUV-UV excitation, UV-vis emission spectra and luminescence decay curves. Furthermore, by constructing the vacuum referred binding energy (VRBE) scheme and applying the frequency-degenerate vibrational model, the impacts of 5d electron binding energy and electron–phonon coupling on luminescence of Ce 3+ in LYBO are analysed. The results show that the Ce 3+ emission in LYBO possesses a moderate intrinsic thermal stability. With the increase in concentration, the thermal stability of the emission gets worse due to the possible thermally-activated concentration quenching. In addition, the simulation of Ce 3+ emission profile at low temperature reveals that the 4f–5d electronic transitions of Ce 3+ ions can be treated to couple with one frequency-degenerate vibrational mode having the effective phonon energy of ∼257 cm −1 with the corresponding Huang–Rhys parameter of ∼6, which indicates a strong electron–phonon interaction of Ce 3+ luminescence in the Li6 Y(BO3 )3 host. Finally, the X-ray excited luminescence spectrum of the LYBO:5%Ce 3+ phosphor is measured to check the potential scintillator applications.